Remarks on ISRU and ISFR Technologies for Manned Missions on Moon and Mars - A. Concas; G. Corrias; R. Orru; R. Licheri; M. Pisu; G. Cao (Eurasian Chemico-Technological Journal, 2012)
Space colonization and exploitation of extra-terrestrial natural resources could help humanity in facing various Earth problems. In this regard, production of energy and materials starting from Moon and Mars natural resources as well as the transportation of humans in space could be considered the long term remedy to issues such as overpopulation, depletion of fossil fuels, climate change as well as reduction of available natural resources. Along theses lines, two recently filed patents related to use of novel technologies for the in situ exploitation of natural resources available on Moon and Mars have been developed.